2013
DOI: 10.1371/journal.pgen.1003373
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Upregulation of lncRNAs at 13q14.3 in Leukemia Is Linked to the In Cis Downregulation of a Gene Cluster That Targets NF-kB

Abstract: Non-coding RNAs are much more common than previously thought. However, for the vast majority of non-coding RNAs, the cellular function remains enigmatic. The two long non-coding RNA (lncRNA) genes DLEU1 and DLEU2 map to a critical region at chromosomal band 13q14.3 that is recurrently deleted in solid tumors and hematopoietic malignancies like chronic lymphocytic leukemia (CLL). While no point mutations have been found in the protein coding candidate genes at 13q14.3, they are deregulated in malignant cells, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
146
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 103 publications
(155 reference statements)
2
146
0
1
Order By: Relevance
“…First, genomic loci producing non-coding transcripts are subject to epigenetic regulation similar to that of protein-coding genes. [38][39][40][41][42] Therefore, as with coding genes, environmental influences can lead to changes in their expression and to functional disturbances. We can include in this category the transcription of lncRNAs designated as "signals," 12 as these are examples of activity-dependent, sequence-independent changes in gene expression.…”
Section: Defining Epigeneticsmentioning
confidence: 99%
“…First, genomic loci producing non-coding transcripts are subject to epigenetic regulation similar to that of protein-coding genes. [38][39][40][41][42] Therefore, as with coding genes, environmental influences can lead to changes in their expression and to functional disturbances. We can include in this category the transcription of lncRNAs designated as "signals," 12 as these are examples of activity-dependent, sequence-independent changes in gene expression.…”
Section: Defining Epigeneticsmentioning
confidence: 99%
“…1 In addition, CLL cells harbor genome-wide aberrant DNA-methylation. 2 Of interest, in CLL, DNA-methylation of single CpGs overall correlated only weakly with gene expression. However, no detailed analysis of DNA-methylation on single gene level was performed that would also take larger regions into account.…”
mentioning
confidence: 99%
“…lncRNAs may be classified according to their mode of action and their functions in cells, including genetic imprinting (14,15), modulating the cancer epigenome (9), serving as molecular decoys (16) and post-transcriptional regulation (10). Accumulating evidence has shown that lncRNA expression profiling may facilitate the diagnosis and prognosis of human cancer, including bladder cancer (17), leukemia (18), breast cancer (9) and rectal cancer (19), suggesting that lncRNAs may serve as effective therapeutic targets for intervention. Previous evidence indicates that lncRNAs are important in the pathogenesis of glioma, including HOTAIR (20), H19 (21) and Linc-POU3F3 (8 been annotated, only a few lncRNAs have been functionally characterized in glioma.…”
Section: Introductionmentioning
confidence: 99%